2020
DOI: 10.3897/zookeys.945.39044
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist and integrative biodiversity discovery of barnacles (Crustacea, Cirripedia) from the Moluccas, East Indonesia

Abstract: To contribute to the taxonomic knowledge of barnacles in this understudied area, the first checklist of barnacles from the Moluccas is presented, including additional information on morphology, distribution, and substrate as well as molecular data. The species of barnacles from the Moluccas have been determined using morphological analysis and DNA sequences. During 19 field trips conducted between January 2016 and September 2017, 1,513 specimens of 24 species of intertidal and one species of deep-sea b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Based on the overview scans showing all barnacle specimens situated in each sponge, we could estimate which parts of the sponge to dissect to obtain a specific barnacle specimen. Morphological characters of the hard body parts (parietes and opercular plates) and soft body parts (mouthparts, six pairs of cirri, and penis) were examined as in Pitriana et al (2020). Species were identified based on Lamarck (1818), Darwin (1854), Krüger (1911), Hoek (1913), Broch (1931), Rosell (1991), and Kolbasov (1993).…”
Section: Specimen Direct Morphological Examinationmentioning
confidence: 99%
“…Based on the overview scans showing all barnacle specimens situated in each sponge, we could estimate which parts of the sponge to dissect to obtain a specific barnacle specimen. Morphological characters of the hard body parts (parietes and opercular plates) and soft body parts (mouthparts, six pairs of cirri, and penis) were examined as in Pitriana et al (2020). Species were identified based on Lamarck (1818), Darwin (1854), Krüger (1911), Hoek (1913), Broch (1931), Rosell (1991), and Kolbasov (1993).…”
Section: Specimen Direct Morphological Examinationmentioning
confidence: 99%
“…Balanidae is divided into Balaninae, Amphibalaninae, and Megabalaninae (Pitombo 2004). Nevertheless, Pitriana et al (2020) was only found two families in Mollucas waters, namely Amphibalaninae and Megabalaninae.…”
Section: Introductionmentioning
confidence: 98%
“…Henry and McLaughlin (1975) stated that the genera are different in denticles in the labrum and in the color pattern of the parietal and sheath in Amphibalanus. In the period in which Amphibalanus belonged to Balanus, a Balanus amphitrite complex was described (Pitriana et al 2020). Later, the Balanus amphitrite complex was further identified and divided into three nominal species: Amphibalanus amphitrite (Pitombo 2004;Chen et al 2014;Shahdadi et al 2014;Pochai et al 2017), A. reticulatus (Pitombo 2004;Pochai et al 2017) and A. variegatus (Pitombo 2004;Horikoshi and Okamoto 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations